Draft Genome Sequence of the Mannitol-Producing Strain Lactobacillus mucosae CRL573 - Bleckwedel, Juliana (2014)
Lactobacillus mucosae CRL573, isolated from child fecal samples, efficiently converts fructose and/or sucrose into the lowcalorie sugar mannitol when cultured in modified MRS medium at pH 5.0. Also, the strain is capable of producing bacteriocin. The draft genome sequence of this strain with potential industrial applications is presented here.